A REVIEW OF INVASIVE SKIN REJUVENATION METHODS IN AESTHETIC MEDICINE - Dorota Plechawska; Joanna Gerlach; Natalia Guzik; Joanna Kaźmierczak; Anna Mandecka; Kornela Kotucha-Cyl; Weronika Komala; Karolina Witek; Marta Nowocień (International Journal of Innovative Technologies in Social Science, 2025)
Invasive skin rejuvenation techniques such as microneedling, platelet-rich plasma (PRP), and fractional lasers are gaining popularity in aesthetic medicine. Their action is based on the stimulation of skin repair processes, primarily by stimulating collagen and elastin synthesis. Microneedling, also known as collagen induction therapy, improves skin structure and elasticity through controlled mechanical micro-damage. PRP, containing autologous growth factors, supports cellular regeneration and is used both as a monotherapy and in combination therapy. Fractional lasers—both ablative and non-ablative—operate through precise, thermal damage to the skin, enabling the treatment of wrinkles, scars, and discoloration. Despite their high effectiveness confirmed in clinical trials, limitations such as small patient groups, lack of standardized treatment protocols, and short follow-up periods hinder a comprehensive assessment of their effectiveness. The use of combined therapies demonstrates synergistic effects and may be an optimal treatment strategy for patients seeking lasting results while maintaining a high level of safety.Study Purpose and Materials: The aim of this study is to analyse clinical trials published in the PubMed database between 2008 and 2025 regarding invasive skin rejuvenation techniques. This field is a rapidly developing area of aesthetic medicine, offering new therapeutic options for patients with signs of skin aging. The study focuses on assessing the effectiveness, safety profile, and clinical indications of three main methods: microneedling, platelet-rich plasma (PRP) therapy, and fractional lasers.Summary: Microneedling, platelet-rich plasma (PRP), and fractional lasers are effective and safe methods of invasive skin rejuvenation. Their use, both as monotherapy and in combination therapies, improves skin quality and reduces wrinkles, scars, and discoloration. Despite promising clinical results, further studies with larger patient groups and standardized protocols are necessary to solidify their place in everyday aesthetic medicine practice.